Sensors and actuators SP-737 (Society of Automotive Engineers, 1988)
A new era of application for the wiegand effect - Non-contacting sensors for automotive applications - MRE-Type non-contact position sensor - Wheel rotation sensor for navigation system - Semiconductor device simulation of solid state relay "Power MOSFETs" - Silicon semiconductor pressure sensor for high pressure use - Automotive pressure transducer for underhood applications - A system approach to smart-sensors and smart-actuators design - Automotive specific application of sensor-systems with suitable technologies and appropriate housings - New sensor concepts using vibrating cantilevers - Multi layered zirconia oxygen sensor with modified rhodium catalyst electrode - Mixture formation of fuel injection systems in gasoline engines - Hot.film air mass meter. A low-cost approach to intake air measurement - Frequency domain characterization of mass air flow sensors - A portable fast response air-fuel ratio meter using an extended range oxygen sensor.